The Listeria monocytogenes Bile Stimulon under Acidic Conditions Is Characterized by Strain-Specific Patterns and the Upregulation of Motility, Cell Wall Modification Functions, and the PrfA Regulon - Guariglia-Oropeza, Veronica; Orsi, Renato H.; Guldimann, Claudia; Wiedmann, Martin; Boor, Kathryn J. (Frontiers in Microbiology, 2018)
Listeria monocytogenes uses a variety of transcriptional regulation strategies to adapt to the extra-host environment, the gastrointestinal tract, and the intracellular host environment. While the alternative sigma factor SigB has been proposed to be a key transcriptional regulator that facilitates Listeria monocytogenes adaptation to the gastrointestinal environment, the L. monocytogenes’ transcriptional response to bile exposure is not well understood. RNA-seq characterization of the bile stimulon was performed in two L. monocytogenes strains representing lineages I and II. Exposure to bile at pH 5.5 elicited a large transcriptomic response with approx. 16% and 23% of genes showing differential transcription in 10403S and H7858, respectively. The bile stimulon includes genes involved in motility and cell wall modification mechanisms, as well as genes in the PrfA regulon, which likely facilitate survival during the gastrointestinal stages of infection that follow bile exposure. The fact that bile exposure induced the PrfA regulon, but did not induce further upregulation of the SigB regulon (beyond that expected by exposure to pH 5.5), suggests a model where at the earlier stages of gastrointestinal infection (e.g., acid exposure in the stomach), SigB-dependent gene expression plays an important role. Subsequent exposure to bile induces the PrfA regulon, potentially priming L. monocytogenes for subsequent intracellular infection stages. Some members of the bile stimulon showed lineage- or strain-specific distribution when 27 Listeria genomes were analyzed. Even though sigB null mutants showed increased sensitivity to bile, the SigB regulon was not found to be upregulated in response to bile beyond levels expected by exposure to pH 5.5. Comparison of wildtype and corresponding ΔsigB strains newly identified 26 SigB-dependent genes, all with upstream putative SigB-dependent promoters.